Very metal-poor stars observed by the RAVE survey - Matijevič, Gal; Grebel, Eva K. (Astronomy and astrophysics, 2017)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics
Gesehen am 13.09.2017